Relasi Agama Dan Masyarakat Dalam Perspektif PAK - Imanuela Pandu; Nexien Richard Maitimu (P3M POLITEKNIK NEGERI AMBON, 2025)
Religion is a symbol of sacredness and protects humans from chaos, despair, and other unpleasant situations. Religion plays a crucial role in Indonesian society for human survival. Religion itself signifies order and harmony. By embracing religion, personal and community life is expected to be more peaceful and orderly, as individuals have a guiding principle. This article uses a qualitative research approach with qualitative descriptive analysis. Furthermore, a literature review approach was used to obtain sources to supplement the research data. Keywords: Relations, Religion, Society and Christian Education